2017
DOI: 10.1186/s13054-017-1873-0
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic estimated glomerular filtration rate in critically ill patients: beyond the acute kidney injury severity classification system

Abstract: BackgroundAlthough significant advances have been achieved in acute kidney injury (AKI) research following its classification, potential pitfalls can be identified in clinical practice. The nonsteady-state (kinetic) estimated glomerular filtration rate (KeGFR) could add clinical and prognostic information in critically ill patients beyond the current AKI classification system.MethodsThis was a retrospective analysis using data from the Multiparameter Intelligent Monitoring in Intensive Care II project. The KeG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Kinetic eGFR magnifies the change between the last sCr value and the present one, and can, therefore, overcome the delay in detection of kidney function changes seen with a single measurement of sCr or regular eGFR based on sCr at one time‐point. Kinetic eGFR is previously reported to be useful in the early prediction of delayed graft function (DGF) within 4 h of renal transplantation, prediction of short‐term renal recovery after AKI, and identifying risks for RRT requirement during ICU stay and hospital mortality . In this preliminary study, we introduced the possibility that kinetic eGFR can be used as a predictor for CRRT discontinuation in addition to the conventional parameters including urine volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic eGFR magnifies the change between the last sCr value and the present one, and can, therefore, overcome the delay in detection of kidney function changes seen with a single measurement of sCr or regular eGFR based on sCr at one time‐point. Kinetic eGFR is previously reported to be useful in the early prediction of delayed graft function (DGF) within 4 h of renal transplantation, prediction of short‐term renal recovery after AKI, and identifying risks for RRT requirement during ICU stay and hospital mortality . In this preliminary study, we introduced the possibility that kinetic eGFR can be used as a predictor for CRRT discontinuation in addition to the conventional parameters including urine volume.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic eGFR is previously reported to be useful in the early prediction of delayed graft function (DGF) within 4 h of renal transplantation, 19 prediction of short-term renal recovery after AKI, 20 and identifying risks for RRT requirement during ICU stay and hospital mortality. 21 In this preliminary study, we introduced the possibility that kinetic eGFR can be used as a predictor for CRRT discontinuation in addition to the conventional parameters including urine volume. We also proposed discontinuation index (DI) for clinical utility.…”
Section: Discussionmentioning
confidence: 99%
“…De Oliveira Marques et al [13] found that KeGFR did not correlate with AKI severity in their ICU cohort but the worst achieved KeGFR conferred an incremental risk of death in a stepwise manner. However, this study excluded patients with an initial MDRD GFR of < 30 mL/ min and/or a Cr of > 4 mg/dL.…”
Section: Discussionmentioning
confidence: 92%
“…The KeGFR equation has been applied in recent studies involving patients in ICU, post-operative patients, and renal transplant recipients [13][14][15][16]. The common characteristic of the study subjects in these patient cohorts is inhospital AKI with known renal injury onset time.…”
Section: Doi: 101159/000492439mentioning
confidence: 99%
See 1 more Smart Citation